ANALISIS DAMPAK KECANDUAN GAME ONLINE TERHADAP KOMUNIKASI INTERPERSONAL SISWA SMA MENGGUNAKAN TEORI OPERANT CONDITIONING - agwila abata; Serdianus Serdianus (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2025)
Online game addiction is a growing form of behavioral addiction, particularly prevalent among teenagers and young adults. This addiction arises due to positive and negative reinforcements gained during gameplay, as explained in B.F. Skinner’s Operant Conditioning theory. Positive reinforcement includes achievements such as level progression, points, or praise from online peers, while negative reinforcement involves using games as an escape from academic stress or social problems. A lack of effective punishment or control from the surrounding environment worsens the addictive behavior. One of the most significant consequences is the disruption of interpersonal communication. Individuals with online game addiction tend to prioritize virtual interaction over real-life communication, leading to a decline in empathy, active listening, and emotional expression. Over time, this may damage relationships with family, friends, and social circles, and contribute to feelings of loneliness and isolation. Therefore, understanding the impact of online game addiction on interpersonal communication is crucial to promoting awareness and encouraging balanced social interaction in daily life.